ANALISIS DAMPAK IMPLEMENTASI KEGIATAN P5 TERHADAP LITERASI BUDAYA BAGI SISWA DAN GURU - Anggie Barokah; Daniswara Rifansa Al Rafi; Fatika Deby Aszahra; Febryana, Zega; Yosafat Hermawan Trinugraha; Bagas Narendra Parahita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Penguatan Profil Pelajar Pancasila Project (Strengthening the Profile of Pancasila Student) or P5 is a forum for students in developing their interests and talents. This research intended to examine the influence of the P5 project activities on students’ cultural literacy in Solo-Raya. The Systematic Literature Review (SLR) was employed as a research approach, collecting and analyzing numerous sources of related literature. The research’s findings reveal that P5 activities significantly improve students’ comprehension of cultural literacy through a variety of ways, including collaborative learning, strengthening local values, and integrating arts into the curriculum. By implementing these activities not only improves students’ comprehension of cultural history but also fosters a sense of respect and preservation for local culture. This research is designed to serve as a model for developing a more successful curriculum for incorporating cultural literacy into Indonesian education.